Деформационное упрочнение стали с бейнитной структурой - Громов В. Е. Виктор Евгеньевич; Никитина Е. Н.; Иванов Ю. Ф. Юрий Федорович; Аксенова К. В. Крестина Владимировна; Корнет Е. В. Евгений Владимирович (2015, 2015)
Заглавие с экрана